PENINGKATAN PRESTASI BELAJAR IPA MELALUI PEMBELAJARAN KOOPERATIF TIPE STUDENT FACILITATOR AND EXPLAINING SISWA KELAS IXE SMP NEGERI 01 WONOASRI KABUPATEN MADIUN TAHUN PELAJARAN 2013/2014 - Suhendariyanti Suhendariyanti (Florea : Jurnal Biologi dan Pembelajarannya, 2014)
Science Skills include observing skills with all the senses, using tools and materials, planned the experiment, ask questions and formulate hypotheses, conduct experiments, concluded, and communicate findings. Application of learning methods Student Facilitator and Explaining in science subjects can be done relatively easily by a teacher. The purpose of research is to improve science learning achievement through the use of cooperative learning model Student Facilitator and Explaining. Classroom action research with the stages of planning (planning), implementation (acting), observation (obseving), and reflection (relecting). The data were analyzed descriptively. Based on the results obtained by the action hypothesis first cycle the average value of learning achievement 70.63 cycle II the average value of learning achievement 80.63. Conclusion of the study there was an increase science learning achievement with cooperative learning Student Facilitator and Explaining.